Pola Komunikasi UPT Perpustakaan IAIN Madura Dalam Melayani Kebutuhan Mahasiswa Di Masa Pandemi - Safira Nur Laily (Institut Agama Islam Negeri Kendari, 2022)
The Covid 19 pandemic resulted in the issuance of a Work From Home (WFH) policy by the government. This caused the library service system to change to online. Based on this, this research wants to examine First, what are the communication patterns of UPT Library IAIN Madura in serving the needs of students during a pandemic. Second, what are the inhibiting and supporting factors for the communication patterns implemented by the UPT Library of IAIN Madura in serving the needs of students during a pandemic. This study uses a qualitative method with a descriptive approach, namely studying and describing the communication patterns of UPT Library IAIN Madura in serving the needs of students during a pandemic. In the data collection process, the methods used were observation, interviews, and documentation. From the results of the study, researchers found several communication patterns used. First, mass communication or secondary communication patterns. The second is interpersonal communication, and the last is a two-way communication pattern. Meanwhile, there are two factors in the application of this communication pattern, namely supporting and inhibiting factors. Supporting factors are the existence of an adequate wifi network and the information conveyed using fun, clear and solid language. While the inhibiting factors are sudden power outages and the sensitivity of students in absorbing circulating information so that there are many misinterpretations. Keywords: Patterns of communication, Covid 19 Pandemic, Libraries, IAIN Madura